Medios audiovisuales y su incidencia en la enseñanza-aprendizaje del idioma inglés en los estudiantes de básica superior de la unidad educativa 24 de mayo del cantón Quevedo. - Carriel López, Ileana Jessenia (2016)
This research is based on an institutional problem that affects one way or another in obtaining meaningful learning and quality in the area of English. In the Education Unit on May 24, teachers in the area do not have the resources necessary for mutual learning is more effective, but it is important that these quality assurance designing strategies in the use of audiovisual media for students to take advantage of these resources and achieve skills and skills required. While it is English is more effective with the interaction of complementary means it is important to know them use (Meza, 2011) in his research on the audiovisual media in education tells us that these are directly concerned with the image as photography and audio, and refer especially teaching aids, with images and recordings, serve to communicate a specific message learning. That said this has methodological alternatives to be used by teachers and students to learn English language is far more effective and so the objectives set at the beginning of the year are achieved, and can function in their daily and professional life.